2004
DOI: 10.1093/ndt/gfh1045
|View full text |Cite
|
Sign up to set email alerts
|

Do we need screening for thrombophilia prior to kidney transplantation?

Abstract: Background. There is increased risk for the occurrence of deep venous thrombosis (DVT) and renovascular thrombosis after kidney transplantation. A disruption of the blood homeostasis caused by surgery and leading to clotting and bleeding malfunctions is widely accepted. However, other causes such as inherited or acquired disorders of the clotting system may further increase the risk of thrombosis. Here, we summarize and review data on possible causes, incidence and ways to prevent the occurrence of DVT and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 39 publications
0
31
0
3
Order By: Relevance
“…12 Transplant renal artery/vein thrombosis generally occurs during the first 2 postoperative weeks and is reported in up to 6% of kidney transplants. 13,14 In pediatric kidney transplant, graft loss due to thrombosis is a major problem. 15 According to the data from the North American Pediatric Renal Transplant Cooperative Study, vascular thrombosis accounts for 11.6% of graft losses in pediatric renal transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Transplant renal artery/vein thrombosis generally occurs during the first 2 postoperative weeks and is reported in up to 6% of kidney transplants. 13,14 In pediatric kidney transplant, graft loss due to thrombosis is a major problem. 15 According to the data from the North American Pediatric Renal Transplant Cooperative Study, vascular thrombosis accounts for 11.6% of graft losses in pediatric renal transplant.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several investigators have reported a dramatic increase in the incidence of renovascular thrombosis among cyclosporine-treated renal transplant recipients when compared with recipients treated with prednisone and azathioprine only. [23][24][25] Interestingly, a prospective multicenter study showed no significant difference regarding the occurrence of renovascular thrombosis under cyclosporine versus azathioprine.…”
Section: Discussionmentioning
confidence: 99%
“…When the disorder is diagnosed in pretransplant assessment, anticoagulation therapy must be initiated immediately. 10,11 Low molecular weight heparin, unfractionated heparin, or warfarin may be used in doses that provide therapeutic effect. Because of renal deficiency, titration and individualization of doses are necessary to achieve target therapeutic levels, which differ depending on the anticoagulant agent used.…”
Section: Discussionmentioning
confidence: 99%
“…Because of renal deficiency, titration and individualization of doses are necessary to achieve target therapeutic levels, which differ depending on the anticoagulant agent used. 10,11 Repeated measurements either of anti Xa levels or aPTT or INR, and hence dose titration, are necessary not only to prevent thrombotic events perioperatively but also, to prevent postoperative hemorrhage in recipients with thrombophilic disorders. 12,13 In children with thrombophilia the incidence of graft thrombosis is higher than adults considering the fact that renal transplant in children with endstage renal disease has already 11.6% risk of acute graft thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of 502 end-stage renal disease patients 11 of 23 patients identified with APS underwent transplant. 47,48 All 7 who did not receive peri-operative anticoagulation lost their grafts within 1 week of transplant due to thrombosis, whereas 3 of 4 who received prophylactic anticoagulation maintained long-term graft function. Importantly, none of the 37 patients with only serologic evidence of antiphospholipid antibodies but no prior history of clinical thrombosis received anticoagulation.…”
Section: Organ Transplantationmentioning
confidence: 99%